1998
DOI: 10.2737/rmrs-rp-11
|View full text |Cite
|
Sign up to set email alerts
|

Responses of cavity-nesting birds to stand-replacement fire and salvage logging in ponderosa pine/Douglas-fir forests of southwestern Idaho

Abstract: long-term studies on how cavity-nesting birds respond to different fire conditions in ponderosa pine1Douglas-fir forests of western Idaho. The work was started in response to the high-intensity wildfires of 1992 and 1994 on the Boise National Forest. This publication provides information to managers and biologists on the effects of stand-replacement wildfire (a no-action alternative to the Forest Health Initiative [USDA 1994a1) and salvage logging on cavity-nesting birds.Cavity-nesting birds were selected for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
148
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(164 citation statements)
references
References 17 publications
14
148
2
Order By: Relevance
“…As decay fungi soften the wood of fire-killed trees, more snags become available for nest sites. The snags and trees preferred for excavating in the first few years after fire are best identified by their large size and broken tops (Hutto 1995, Saab andDudley 1998).…”
Section: Northern Goshawkmentioning
confidence: 99%
“…As decay fungi soften the wood of fire-killed trees, more snags become available for nest sites. The snags and trees preferred for excavating in the first few years after fire are best identified by their large size and broken tops (Hutto 1995, Saab andDudley 1998).…”
Section: Northern Goshawkmentioning
confidence: 99%
“…Moreover, suggested that Black-backed Woodpeckers use an 'island-hop' strategy, exploiting one high-quality burn after another and, when recently burned habitats are scarce, 'survive' in unburned forests until recently burned stands become available (Murphy and Lenhausen, 1998;. This suggests that unburned forests are only important to Biack-backed Woodpeckers at times when suitable recently burned forests are unavailable Saab and Dudley, 1998;. Because of this view, the practice of post-fire salvage logging has been strongly criticized, as it is perceived as eliminating potential optimal habitat for this species (Hannon and Drapeau, 2005).…”
Section: Objectifs De L'étude Et Structure De La Thèsementioning
confidence: 99%
“…Despite the assumptions outlined above, little information exists regarding the nesting ecology of Black-backed Woodpeckers in burned (but see Saab and Dudley, 1998;Saab et al, 2004Vierling et al, 2008) and unburned habitats (but see . Theoretically, lower foraging opportunities in unburned forest stands could reduce the amount of food delivered to nestlings, so increasing internestling competition (Hadow, 1976).…”
Section: Objectifs De L'étude Et Structure De La Thèsementioning
confidence: 99%
“…In Idaho, nesting densities were more than double in unlogged post-burn forests compared to harvested areas in the same burn (Saab and Dudley 1998). This result was true when all or half of the merchantable trees were removed post-fire.…”
Section: 2009)mentioning
confidence: 99%